Expression and regulation of the NALP3 inflammasome complex in periodontal diseases - Bostanci, N.; Emingil, G.; Saygan, B.; Turkoglu, O.; Atilla, G.; Curtis, M. A.; Belibasakis, G. N. (Clinical and experimental immunology, 2009)
Summary Periodontitis is an infectious process characterized by inflammation affecting the supporting structures of the teeth. Porphyromonas gingivalis is a major oral bacterial species implicated in the pathogenesis of periodontitis. Processing of interleukin (IL)‐1 family cytokines is regulated by an intracellular innate immune response system, known as the NALP3 [nacht domain‐, leucine‐rich repeat‐, and pyrin domain (PYD)‐containing protein 3] inflammasome complex. The aim of the present study was to investigate by quantitative real‐time polymerase chain reaction (PCR) the mRNA expression of NALP3, its effector molecule apoptosis associated speck‐like protein (ASC), its putative antagonist NLRP2 (NLR family, PYD‐containing protein 2), IL‐1β and IL‐18 (i) in gingival tissues from patients with gingivitis (n = 10), chronic periodontitis (n = 18), generalized aggressive periodontitis (n = 20), as well as in healthy subjects (n = 20), (ii) in vitro in a human monocytic cell line (Mono‐Mac‐6), in response to P. gingivalis challenge for 6 h. The clinical data indicate that NALP3 and NLRP2, but not ASC, are expressed at significantly higher levels in the three forms of inflammatory periodontal disease compared to health. Furthermore, a positive correlation was revealed between NALP3 and IL‐1β or IL‐18 expression levels in these tissues. The in vitro data demonstrate that P. gingivalis deregulates the NALP3 inflammasome complex in Mono‐Mac‐6 cells by enhancing NALP3 and down‐regulating NLRP2 and ASC expression. In conclusion, this study reveals a role for the NALP3 inflammasome complex in inflammatory periodontal disease, and provides a mechanistic insight to the host immune responses involved in the pathogenesis of the disease by demonstrating the modulation of this cytokine‐signalling pathway by bacterial challenge.